The employment consequences of growing up in a dual-parent jobless household: a comparison of Australia and the United States. - Mooi-Reci, Irma; Wooden, Mark; Curry, Matthew (My University, 2020)
Despite the relevance of parents’ economic participation for children’s future outcomes, few studies have considered the joint contribution of both parents’ joblessness in explaining children’s employment outcomes in the long run. Further, previous studies have used measures of parents’ employment status observed at a single point in time. In contrast, in this study, exposure to dual-parent joblessness is measured in a cumulative fashion using longitudinal data for Australia (from the HILDA Survey, N= 895) and the United States (from the PSID,N=1,500). We find that, in both countries, dual-parent-child associations are multiple times greater when parents jointly experience joblessness than when either of the parents is jobless. In the United States, family resources fully account for the link between parents’ and their children’s joblessness, whereas this is not the case in Australia. Overall, our study shows that dual-parent joblessness is an independent dimension of stratification that plays a prominent role in the reproduction of social and economic status across generations.
Research in Social Stratification and Mobility
Keywords: Intergenerational transfer; Labour market